Estudo in vitro da ação da berbamina no vírus Chikungunya (CHIKV) - Bortolato, Isabella do Vale Francisco [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Chikungunya virus (CHIKV) is the causative agent of Chikungunya fever (CHIKF), a disease transmitted mainly by mosquitoes of the genus Aedes. This virus belongs to the group of arboviruses, which includes approximately 500 known species, transmitted by hematophagous arthropods. Despite scientific efforts, there are currently no treatments; however, there are approved vaccines for CHIKV. This study aimed to evaluate the antiviral potential of berbamine and its effects on different stages of the viral replication cycle. Cytotoxicity assays (MTT), with concentrations between 200 and 1.5625 µM in BHK-21 and Huh-7 cells, determined the highest non-cytotoxic concentrations (MCNT), which were 6.25 µM and 12.5 µM, respectively. These concentrations were used in the antiviral tests. In the initial assay with berbamine on MCNTs and using CHIKV CMV NLuc at MOI 0.1 for BHK-21 and MOI 2 for Huh-7, viral inhibition of 77.3% was observed in BHK-21 cells and 94.6% in Huh-7 cells. Subsequently, the dose-dependence assay revealed selectivity indices (SI) of 3.19 for BHK-21 and 4.19 for Huh-7. A time-of-addition assay indicated that berbamine has greater inhibitory activity in the entry and post-entry phases of the viral replication cycle in both cell lines. Furthermore, berbamine demonstrated a virucidal effect by inactivating extracellular virions, with inhibition of 81.3% in Huh-7 and 62.9% in BHK-21. The nsP2 and nsP3 proteins showed significantly lower results in cells treated with berbamine compared to cells treated with the vehicle control, using the Western blotting method, while the energy binding interactions were demonstrated through molecular docking. These results indicate berbamine as a promising candidate in the fight against CHIKV, giving rise to the hypothesis that this compound can inhibit viral replication, inactivate extracellular virions and act on the nsP2 and nsP3 proteins of the virus, which are essential for its replication. Future studies should deepen the investigation of the mechanisms of action of berbamine and explore its development as a potential effective and safe antiviral treatment.

Chikungunya virus (CHIKV) is the causative agent of Chikungunya fever (CHIKF), a disease transmitted mainly by mosquitoes of the genus Aedes. This virus belongs to the group of arboviruses, which includes approximately 500 known species, transmitted by hematophagous arthropods. Despite scientific efforts, there are currently no treatments; however, there are approved vaccines for CHIKV. This study aimed to evaluate the antiviral potential of berbamine and its effects on different stages of the viral replication cycle. Cytotoxicity assays (MTT), with concentrations between 200 and 1.5625 µM in BHK-21 and Huh-7 cells, determined the highest non-cytotoxic concentrations (MCNT), which were 6.25 µM and 12.5 µM, respectively. These concentrations were used in the antiviral tests. In the initial assay with berbamine on MCNTs and using CHIKV CMV NLuc at MOI 0.1 for BHK-21 and MOI 2 for Huh-7, viral inhibition of 77.3% was observed in BHK-21 cells and 94.6% in Huh-7 cells. Subsequently, the dose-dependence assay revealed selectivity indices (SI) of 3.19 for BHK-21 and 4.19 for Huh-7. A time-of-addition assay indicated that berbamine has greater inhibitory activity in the entry and post-entry phases of the viral replication cycle in both cell lines. Furthermore, berbamine demonstrated a virucidal effect by inactivating extracellular virions, with inhibition of 81.3% in Huh-7 and 62.9% in BHK21. The nsP2 and nsP3 proteins showed significantly lower results in cells treated with berbamine compared to cells treated with the vehicle control, using the Western blotting method, while the energy binding interactions were demonstrated through molecular docking. These results indicate berbamine as a promising candidate in the fight against CHIKV, giving rise to the hypothesis that this compound can inhibit viral replication, inactivate extracellular virions and act on the nsP2 and nsP3 proteins of the virus, which are essential for its replication. Future studies should deepen the investigation of the mechanisms of action of berbamine and explore its development as a potential effective and safe antiviral treatment
In vitro study of the action of berbamine on the Chikungunya virus (CHIKV)
Keywords: Arbovírus; Chikungunya; Antiviral; Berbamina; Arboviruses; Chikungunya; Berbamine